Small Museums Change (TU Delft OPEN Publishing, 2025)
What is a ‘small museum’? In this book, the term ‘small’ refers to a museum with a maximum of two ‘normally’ paid full-time functions and further completely staffed by volunteers. People are placed in the centre of the definition, as they should be. This book is part of a series of books produced in cooperation with and financed by the Stichting Rondeltappe-Bernoster-Kemmers. All books of the series have been reviewed and edited by Silvia Naldini, Section of Heritage & Architecture, Faculty of Architecture and the Built Environment, Delft University of Technology, The Netherlands.